Is There Any Differences Between Bmi Body Mass Index (Bmi), Demographics and Clinical Appearance of Patients With Pilonidal Sinus Disease? - Aygen, Erhan; Ayten, Refik (Fırat University, 2003)
Aim: The aim of this study to explain the interaction between the body mass index (BMI) and demographic features for patients with pilonidal sinus. Materials and method: The patients who have pilonidal sinus were divided into two groups. 249 patients were included this retrospective study. Group I referred patients whose BMI were >25 (n=130) and Group II referred patients whose BMI

Amaç: Pilonidal sinüslü hastaların body mass index (BMİ)'leri ile demografik özellikleri arasındaki ilişkiyi ortaya koymak. Gereç ve yöntem: Pilonidal sinüs nedeniyle tedavi edilen 249 hasta, BMİ'lerine göre 25> olanlar Grup I (n=130) ve 25< olanlar ise Grup II (n=119) olacak şekilde iki gruba ayrıldı. Hastalara ait bilgiler bu hastalar için hazırlanmış özel formlardan retrospektif olarak tarandı. Bulgular: Her iki grupta da erkek cinsiyet daha fazla olup Grup I'de bu fark anlamlıydı (p
Pilonidal Sinüs Hastalığında Body Mass Indexe (Bmı) Göre Demografik Özellikler ve Klinik Durum Farklı Mı?